Process mapping in screening mammography...Proceedings of the 16th Symposium for Computer Applications in Radiology. 'PACS: Performance Improvement in Radiology.' Houston, TX, May 6-9, 1999 - Whitman GJ; Venable SL; Downs RL; Garza D; Levy S; Ophir KJ; Spears KF; Sprinkle-Vincent SK; Stelling CB (Journal of Digital Imaging)
Successful screening mammography programs aim to screen large numbers of women efficiently and inexpensively. Development of an effective screening mammography program requires skilled personnel, solid infrastructure, and a robust computer system. A group of physicians, technologists, computer support personnel, and administrators carefully analyzed a growing screening mammography program as a series of steps, starting with the request for the examination and ending with the receipt of a hard-copy consultation. The analysis involved a detailed examination of every step and every possible outcome in the screening process. The information gained through process mapping may be used for identification of systemic and personnel problems, allocation of resources, modification of workplace architecture, and design of computer networks. Process mapping is helpful for those involved in designing and improving screening mammography programs. Viewing a process (i.e., obtaining a screening mammogram) as a series of steps may allow for the identification of inefficient components that may limit growth. Copyright (c) 1999 by W.B. Saunders Company